Discovery of new FXR agonists based on 6-ECDCA binding properties by virtual screening and molecular docking. Issue 10 (20th July 2018) - Giancristofaro, Antonella; Barbosa, Arménio J. M.; Ammazzalorso, Alessandra; Amoia, Pasquale; De Filippis, Barbara; Fantacuzzi, Marialuigia; Giampietro, Letizia; Maccallini, Cristina; Amoroso, Rosa
Abstract : Three novel FXR agonists are reported, one full agonist, more efficient than the endogenous ligand chenodeoxycholic acid, and two partial agonists. Abstract : FXR is a member of the nuclear receptor superfamily, which regulates the expression of various genes involved in bile acid, lipid and glucose metabolism. Targeting FXR with small molecules has been exploited to treat lipid-related disorders and diseases such as cholestasis, gallstones and hepatic disorders. In this work, we expand the existing pool of known FXR agonists using a fast hit-to-lead structure-based pharmacophore and docking screening protocol. A set of 25 molecules was selected after screening a large database of commercial chemicals, and experimental tests were carried out to demonstrate their ability to activate FXR. Three novel FXR agonists are reported, namely, one full agonist, more efficient than the endogenous ligand chenodeoxycholic acid, and two partial agonists.